2013
DOI: 10.3945/jn.113.177667
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Dietary Recommendations Is Associated with Acculturation among Latino Farm Workers

Abstract: We examined adherence to dietary recommendations on fruit/vegetable and fat intake and identified correlates with acculturation indicators as well as with family, lifestyle, and occupational factors in a farm worker cohort in central California. Interviewer-administered questionnaires for this cross-sectional study were completed from January 2006 to April 2007. Participants were 18- to 55-y-old Latinos living in Mendota in a farm worker household. We assessed fruit/vegetable consumption and fat intake using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…All 61 participants were adults who self-identified as Latino with a low-income, with many also reporting a low educational attainment, the mean educational level of the sample being 6th grade (with a standard deviation of 4 grades). The level of acculturation for this community has been reported as “low” [ 46 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 61 participants were adults who self-identified as Latino with a low-income, with many also reporting a low educational attainment, the mean educational level of the sample being 6th grade (with a standard deviation of 4 grades). The level of acculturation for this community has been reported as “low” [ 46 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, among Mexican immigrants residing in the USA, Batis et al ( 5 ) found a mixture of beneficial and harmful changes in dietary patterns, including increased consumption of saturated fat, sugar, salty snacks, pizza and French fries. Moreover, compared with Mexican-Americans born in the USA, those born in Mexico have been found to have a lower intake of fat and a higher intake of fibre and to exhibit greater adherence to nutritional guidelines ( 33 ) , and being born in Mexico or Central America and longer US residency have been found to be associated with higher odds of consuming ≥ 5 daily fruit/vegetable servings ( 7 ) . In Puerto Rican adults residing in Boston area, the association of acculturation with dietary quality was mixed, but tended towards better carbohydrate quality ( 8 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It may not have been a salient issue for this study population because the town is so dominantly Latino, and even though the average length of time in the U.S. was 17 years, acculturation to more general population norms is still very low because of its remote rural location and homogeneously Hispanic residents (Matias et al, 2013). Other literature shows that Mexican immigrants experience a tension between their food experiences growing up in Mexico, where they perceive food to be healthy, and food that is available within the context of their current environment and time availability (Handley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%